The Effect of Benzyl Amino Purine (BAP) and Coconut Water on the Growth of Vanilla (Vanilla planifolia Andrews.) In Vitro - Dwi Erwin Kusbianto; Nurhayadatul Haliza; Didik Pudji Restanto; Distiana Wulanjari; Sholeh Avivi; Mohammad Candra Prayoga (Jurnal Natur Indonesia, 2024)
Vanilla (Vanilla planifolia Andrews.) is one of the plantation crops that has a high selling price, namely wet vanilla IDR 200,000-300,000/kg, regular quality dry vanilla around 1-3 million/kg, and export quality reaching 5-7 million/kg. The opportunity for farmers to develop vanilla commodities in Indonesia is very large, but limited planting materials still hamper it. In-vitro propagation is one technique that can be used to overcome the problem of vanilla propagation in Indonesia. This research aimed to determine the interaction of BAP and coconut water on the growth of vanilla nodal explants in vitro. The method used in this research was a factorial Completely Randomized Design (CRD) with a combination of Benzyl Amino Purine (BAP) and coconut water. The BAP concentration consists of 0 mg/L, 1 mg/L, and 2 mg/L. Coconut water has 0%, 15%, and 30% levels. Data were analyzed using ANOVA and further tested with the DMRT test at a confidence level of 95%. The results showed an interaction between BAP and coconut water on the growth of vanilla explants. The combination treatment of 1 mg/L BAP + 15% coconut water showed the best results with the fastest response time of 8.76+1.53 DAP, average shoot length 2.84±0.70 cm/explant and average root length 0.75±0.07 cm/explant